Precise localization of biliary leak post laparoscopic cholecystectomy with hepatobiliary scintigraphy and adjunct single-photon emission tomography/computed tomography fusion imaging - Shikare, Shekhar; El Hakeem, Ahmed (World Journal of Nuclear Medicine, 2020)
Laparoscopic cholecystectomy is commonly performed as the treatment of choice for symptomatic gallstone diseases. Bile leak is a potential complication of this procedure and the cystic duct stump is the most common site of leakage. Early diagnosis and treatment of bile leak is crucial in decreasing the morbidity and mortality related to this complication. We present a case of biliary leak following laparoscopic cholecystectomy, diagnosis of active biliary leak, and accurate localization of the site of biliary leak on hepatobiliary scintigraphy and adjunct single-photon emission computed tomography/computed tomography fusion imaging.
Keywords: 99mTc-mebrofenin hepatobiliary scintigraphy; biliary leak; endoscopic retrograde cholangiopancreatography; single-photon emission computed tomography/computed tomography imaging